CORPUS-BASED ANALYSIS OF TRANSITION WORDS - Surya, M.Pd., Satyawati (CaLLs (Journal of Culture, Arts, Literature, and Linguistics), 2023)
This study is regarded as a corpus-based investigation which is an empirical study based on corpus linguistics approaches. By using the device of corpora, the investigation over one aspect of writing, that is achieving coherence and cohesion by using transitional signals will be actualized. Corpus approaches are utilized to find the data needed to anchor the usage of transitional signals in producing text or discourse. For this purpose, the researcher would like to find information about the frequency used among the transition words only. The researcher uses a sketch machine of BROWN Corpus to find the data. The aims of the research are: to search for the most order of transitional signal frequency in the English and Indonesian versions; to find out the most order of transitional signal frequency based on the function in English and Indonesian versions. This research belongs to qualitative and quantitative methods. The data found are collected and displayed by using a list of words, table, and description in order to answer the research questions. that the most order of transitional signal frequency in English are: and, but, also, while in the Indonesian version are: dan, juga. The writers of English and Indonesia have the same preference, style, and diction on the function of contrast (but and tetapi), additional information (and, dan), and concluding ideas (finally and pada akhirnya).